Evaluating Implementation of the Early College Model through a Theory of Change. Issue 3 (July 2017) - Allen, Ann; Roberts, J. Kessa
Early College is an initiative aimed at helping first-generation, minority, and low-income students access college courses while they are still in high school. Early College was one of the Race to the Top (RttT) initiatives funded in Ohio. Examining Early College through a change theory lens, we present findings from a two-year case study of Ohio's Early College initiative as to the opportunities and challenges of implementing Early College as an innovation for low-performing schools. Findings from the two sites highlight both similarities and differences according to the context, mission, and vision of the leaders implementing the reform.